2010
DOI: 10.1007/s00267-010-9426-1
|View full text |Cite
|
Sign up to set email alerts
|

Index of Alien Impact: A Method for Evaluating Potential Ecological Impact of Alien Plant Species

Abstract: Alien plant species are stressors to ecosystems and indicators of reduced ecosystem integrity. The magnitude of the stress reflects not only the quantity of aliens present, but also the quality of their interactions with native ecosystems. We develop an Index of Alien Impact (IAI) to estimate the collective ecological impact of in situ alien species. IAI summarizes the frequency of occurrence and potential ecological impact (Invasiveness-Impact Score (I ( i ))) of individual alien species for all aliens presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 77 publications
1
16
0
Order By: Relevance
“…Objective measures are needed for assessing the impacts of different invasive species in a range of habitats to assist in the objective prioritization of species and areas for management (Magee et al. , 2010).…”
Section: Box 2 Priorities For Research On Invasive Alien Trees and Shmentioning
confidence: 99%
See 1 more Smart Citation
“…Objective measures are needed for assessing the impacts of different invasive species in a range of habitats to assist in the objective prioritization of species and areas for management (Magee et al. , 2010).…”
Section: Box 2 Priorities For Research On Invasive Alien Trees and Shmentioning
confidence: 99%
“…Objective measures are needed for assessing the impacts of different invasive species in a range of habitats to assist in the objective prioritization of species and areas for management (Magee et al, 2010). Because woody invasions are becoming Another factor that must be taken into account is the rapidly changing global market for products from trees and shrubs, including new uses.…”
Section: Mapping and Assessing Impactsmentioning
confidence: 99%
“…, 2011). If the range of traits seen in the group is applied to a recent scheme to assess the impacts of plant invasions (Magee et al. , 2010), all taxa are found to have aggressive invasiveness‐impact with the vast majority deemed extreme invasiveness‐impact (Table 3).…”
Section: Approaches To Reducing the Invasion Risk Of Australian Acaciasmentioning
confidence: 99%
“…Many Australian acacias, when invasive, have the potential to rapidly transform ecosystems by fixing nitrogen, changing fire regimes and altering community dynamics . If the range of traits seen in the group is applied to a recent scheme to assess the impacts of plant invasions (Magee et al, 2010), all taxa are found to have aggressive invasiveness-impact with the vast majority deemed extreme invasiveness-impact (Table 3) (Marchante et al, 2008). Restoration efforts must take the impact on ecosystems and ecosystem services into account to increase chances of success .…”
Section: Managing Impactsmentioning
confidence: 99%
“…Furthermore, impact can be defined in various ways , for example as species loss due to invaders (Hejda et al 2009), changes in ecosystem functions (Ehrenfeld 2010;Gutiérrez et al 2014), or economic costs for eradication of non-natives (Pimentel et al 2000). To identify potentially harmful species, researchers as well as practitioners have made great efforts to disentangle mechanisms of invasion (e.g., Rejmánek and Richardson 1996;Lockwood et al 2013), predict invasions (e.g., Kolar and Lodge 2001;van Kleunen et al 2010), and assess their potential impacts (e.g., Magee et al 2010;Dana et al 2014).…”
Section: Introductionmentioning
confidence: 99%